2016
DOI: 10.1038/jp.2016.62
|View full text |Cite
|
Sign up to set email alerts
|

Foley catheter induction of labor as an outpatient procedure

Abstract: Induction of labor by Foley catheter appears suitable for outpatients, and resulted in no differences in cesarean delivery or infection rates compared with in-patients. Most women were satisfied with the outpatient induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 21 publications
3
45
1
Order By: Relevance
“…10 This woman had a normal CTG and induction of labour was continued uneventfully 10 : only data for outpatient group on this adverse events. 10 This woman had a normal CTG and induction of labour was continued uneventfully 10 : only data for outpatient group on this adverse events.…”
Section: Decreased Fetal Movementsmentioning
confidence: 98%
See 4 more Smart Citations
“…10 This woman had a normal CTG and induction of labour was continued uneventfully 10 : only data for outpatient group on this adverse events. 10 This woman had a normal CTG and induction of labour was continued uneventfully 10 : only data for outpatient group on this adverse events.…”
Section: Decreased Fetal Movementsmentioning
confidence: 98%
“…10 They presented with the Foley catheter expulsed in the vagina, and after catheter removal they could urinate normally again. Only one study reported that two women had to return to the hospital because of difficulties urinating at home.…”
Section: Voiding Problemsmentioning
confidence: 99%
See 3 more Smart Citations